Rozważania o wolności twórczości i jej ograniczeniach - Ślęzak, Piotr Arkadiusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2019)
“Creative freedom” belongs to intuitive notions, beyond the attempts to define. Therefore, the author proposes to give up the creation of definition for “creative freedom” within the law . However, he points out constitutive features of human creative activity. They are: “newness” and “mental energy” used for the creation of a new immaterial object. The author indicates the features characterising a creative man also. It is possible to speak about the freedom in the context of human artistic and out of artistic activity. Creative freedom is unlimited .In practice there are the boundaries extralegal and the boundaries defined by the legal norms. The latter were drawn mainly in the RP Constitution, in the copyright law, industrial property law, civil code and penal code.